Determination of the effective permittivity of nanocomposite structures - Nakashidze, Omar; Kalandadze, Lali; Gomidze, Nugzar (International Scientific-practical Conference: „Modern Challenges and Achievements in Information and Communication Technologies“ Transactions, 2026)
This article examines a multicomponent nanodispersed structure consisting of randomly oriented ellipsoidal nanoparticles in a matrix with permittivity ε_m. Formulas for calculating the effective permittivity of such a structure are derived. It is shown that calculating the average particle polarization value is reduced to introducing the effective value of the depolarization factor. The dependence of the effective permittivity of a single-component nanostructure on its structural parameters is studied.